La construcción de viviendas del ministerio de desarrollo urbano y vivienda (MIDUVI) y su incidencia en los niveles de pobreza en las familias del cantón Quevedo. período 2009 - 2014 - Solís Alcívar, Jessenia Johanna (2015)
Quevedo is one of the most important economic and production centers in the province of Los Ríos, its population is approximately 173,575 inhabitants, with an agricultural wealth generated able to boost production to other economic activities of the canton in Quevedo the Ministry of Urban Development and Housing (Housing Ministry) develops important programs to reduce the housing deficit in the country and Quevedo, these programs are: Degree Bonds, Manuela Espejo, Fiscal Housing, Urban and Rural Housing to which will have to meet certain requirements for their application, enforcement and adjudication. In this investigation, it was determined that 43.59% of the beneficiaries of the homes offered by the government, has between4-6 remembers in your family. Whereas 85.90% are happy with the house received from the MIDUVI. The 82.05% of the target population is unemployed, developing a 40.60% in the construction area. The monthly income of the surveyed population by 58.12% are in the range of USD 0 to USD 354, noting the economic and social inclusion of the Government to favor the less affluent class. According to 73.5% of the surveyed population are classified as poor, those mentioned in 86.32% indicated that the Government of Econ. Rafael Correa has reduced the housing deficit, providing them with decent housing, technically built by construction companies, as said 78.63%, benefiting low-income people through employment generation in 88.89%. 84.62% for the cost of housing is normal, while 85.47% felt that the acquisition of a housing reduces poverty